English Effects of sodium butyrate and rosemary leaves on performance, biochemical parameters, immune status, and carcass traits of broiler chickens: Sodium Butyrate and Rosemary on Broiler Growth Performance - Yahya Saifan , Hamed; Abbas Shalaby , Mostafa; Abo-EL-Sooud , Khaled; A. Tony , M.; M. Yassin , Aya (International Journal of Biological Research, 2024)
Effects of sodium butyrate (SB) and rosemary leaves (RL) on growth performance, biochemical profile, immune status, and carcass traits of broiler were evaluated. Fifty-one-day old Hubbard chicks (unsexed) were purchased from Al-Ahram Company for Poultry, Egypt and reared on floor pens in a private farm. The chicks were weighed on arrival and assigned at random into five equal groups, with four replicates each (25 chicks/replicate). Group 1 was fed on a broiler diet without any additions and used as a control. The diets of groups 2 and 3 were supplemented with 500 g/ton SB and 4 kg/ton RL, respectively. In group 4, the diet was enriched with 250g/ton SB plus 2 kg/ton RL. Chicks in group 5 were fed on a diet fortified with 500 g/ton SB plus 4 kg/ton RL. Body weight gain (BWG) and feed efficiency ratio (FER) were determined weekly. Biochemical indexes, immune system function, and carcass traits were determined. The results revealed that supplementing broiler diet with 500g/ton SB plus 4 kg/ton RL increased BWG and FER of birds. This diet decreased serum levels of aspartate aminotransferase, (AST) alanine aminotransferase (ALT), total cholesterol (TC), triglycerides (TG), malondialdehyde (MDA and increased superoxide dismutase (SOD), catalase (CAT), and immunoglobulins. It also boosted immunity as it elevated phagocytic activity, phagocytic index, lysozyme activity, and nitric oxide (NO) concentrations. Antibody titers against Newcastle disease virus were elevated. It can be concluded that supplementing broiler diet with 500g/ton SB plus 4 kg/ton RL improve performance, normalize biochemical profile, and boost immunity.
Keywords: Sodium Butyrate; Rosemary; Broiler Performance; Biochemistry; Immunity.